Influence of Seasonality and Circulating Cytokines on Serial QuantiFERON Discordances. (12th March 2018) - Griffin, Marsha L.; Agarwal, Saroochi; Murphy, Melissa Zhu; Teeter, Larry D.; Graviss, Edward A.
Abstract : Objectives. An 18-month prospective study serially tested healthcare workers (HCWs) for tuberculosis infection (TBI) and reported discordant QuantiFERON Gold In-Tube® (QFT) results in some participants. The purpose of the current study was to investigate whether the interferon-gamma (IFN- γ ) measured by QFT in discordant individuals could be influenced by other circulating cytokines that vary seasonally at the time of phlebotomy. Methods. The CDC funded TBESC Task Order 18 (TO18) project to assess the use of Interferon Gamma Release Assays (IGRAs), T-SPOT. TB ® and QFT, compared to the tuberculin skin test (TST) for the serial testing of TBI in HCW at 4 US sites. Unstimulated plasma from 9 discordant TO18 participants at 4 different time points from the Houston site was multiplexed to determine the association between circulating cytokines and antigen stimulated IFN- γ levels. Results. IL-12, IL-1 β, IL-3, GCSF, and IL-7 were associated with the amount of IFN- γ measured in response to antigen stimulation. In addition to these cytokines, a significant relationship was found between a positive QFT result and the spring season. Conclusions. Allergens during the spring season can result in the upregulation of IL-1 β and IL-3, and this upregulation was observed with the amount of IFN- γ measured in discordant results.